2022
DOI: 10.1051/0004-6361/202243851
|View full text |Cite
|
Sign up to set email alerts
|

The IACOB project

Abstract: Context. Stellar rotation is of key importance in the formation process, the evolution, and the final fate of massive stars. Aims. We perform a reassessment of the empirical rotational properties of Galactic massive O-type stars using the results from a detailed analysis of ground-based multi-epoch optical spectra obtained in the framework of the IACOB & OWN surveys. Methods. Using high-quality optical spectroscopy, we established the velocity distribution for a sample of 285 apparently single and single-line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 89 publications
2
38
0
Order By: Relevance
“…main sequence stars with masses in the range of ∼20-80 M ). This study was partly motivated by the necessity to provide an explanation for an empirical result already highlighted by Conti & Ebbets (1977), Wolff et al (1982) and subsequently confirmed by some other authors (see further references in Simón-Díaz & Herrero 2014;Ramírez-Agudelo et al 2013;Holgado et al 2022); namely: the spin-rate distribution of any investigated (large) sample of O-type stars (even in different metallicity environments) is characterised by a main component, including stars spinning with projected rotational velocities (v sin i) below ∼150-200 km s −1 , and a tail of fast rotators reaching values of v sin i up to 400-600 km s −1 . Such a tail of fast rotators normally comprises ∼20-25% of stars in the considered samples.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…main sequence stars with masses in the range of ∼20-80 M ). This study was partly motivated by the necessity to provide an explanation for an empirical result already highlighted by Conti & Ebbets (1977), Wolff et al (1982) and subsequently confirmed by some other authors (see further references in Simón-Díaz & Herrero 2014;Ramírez-Agudelo et al 2013;Holgado et al 2022); namely: the spin-rate distribution of any investigated (large) sample of O-type stars (even in different metallicity environments) is characterised by a main component, including stars spinning with projected rotational velocities (v sin i) below ∼150-200 km s −1 , and a tail of fast rotators reaching values of v sin i up to 400-600 km s −1 . Such a tail of fast rotators normally comprises ∼20-25% of stars in the considered samples.…”
Section: Introductionmentioning
confidence: 73%
“…Simón-Díaz) to provide solid empirical foundations to our knowledge about the physical properties and evolution of massive OB-type stars (see e.g. Simón-Díaz & Herrero 2014;Simón-Díaz et al 2017;Holgado et al 2020Holgado et al , 2022, in this paper, we perform a complete and homogeneous search for empirical signatures of binarity in a statistically meaningful sample of several tens of fast-rotating Galactic O-type stars. Our ultimate goal is to evaluate the scenario proposed by de Mink et al ( , 2014 to explain the existence of a tail of fast rotators in this stellar domain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though these velocity choices have been inherited from investigations of lower-mass stars, they are very effective in fitting the spectral lines of hot massive stars (Simón-Díaz et al 2010Holgado et al 2022). However, because the turbulent surfaces of massive stars are significantly different to those of their low-mass counterparts (Jiang et al 2018;Schultz et al 2020Schultz et al , 2022, it is uncertain just how accurate the inferred ξ and v macro will be, based on the existing line-fitting approach.…”
Section: Introductionmentioning
confidence: 99%
“…Among other massive stars, a number of weakwind O stars were investigated for the presence of magnetic fields via two large spectropolarimetric surveys, the B fields in OB stars (BOB; Morel et al 2015;Fossati et al 2015;Schöller et al 2017) and the Magnetism in Massive Stars (MiMeS) surveys (Wade et al 2016). Finally, the availability of larger samples of high-resolution spectra of O stars, in particular from the IACOB project -including many weak-wind objects -led to mass quantitative analyses, for example with respect to rotational velocities and additional line-broadening effects (Simón-Díaz & Herrero 2014) and stellar parameters (Holgado et al 2018(Holgado et al , 2022.…”
Section: Introductionmentioning
confidence: 99%